Problem-Based E-Module Integrated with STEM and Assisted by LMS to Foster Creative Thinking Ability - Sari, Meisita; Andra, Doni; Distrik, I Wayan; Aleksandervic, Kurakin Sergei (Universitas Islam Negeri Raden Intan Lampung, 2022)
Appropriate learning resources are required when delivering problem-based physics materials integrated with STEM (Science, Technology, Engineering, and Mathematics). This research aims to create a valid, practical, and effective problem-based e-module integrated with STEM and supported by an LMS (Learning Management System) to train creative thinking skills on harmonic vibration material. The 4-D development model was used in this research (define, design, development, and disseminate). The study of tenth-grade students from class MIA 1 at SMA Muhammadiyah 1 Purbolinggo revealed that the developed e-module had a content validity test result of 89 % and a constructs test result of 88%. The practicality test of the readability aspect yielded an 80% result, and the implementation yielded a 79.07% result.Furthermore, the n-gain value for the effectiveness test based on improvement was 0.54 in the medium category. Furthermore, there was a difference in average pretest and posttest scores with less than 0.05. It is possible to conclude that the developed e-module is appropriate for training students' creative thinking skills. Further researchers are expected to develop platform-assisted e-modules that are more interactive and easier to use in future research.